UJI DOSIS TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) TERHADAP BIBIT GAHARU (Aquilaria malaccensis) - Khairir Rusyadi; Fifi Puspita; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the effect and dose of the best TKKS Trichocompost on agarwood (Aquilaria malaccensis) seedling growth. The research was conducted at the Laboratory of Ecophysiology and in Faculty of Agriculture experimental field University of Riau in July to October 2014 using a completely randomized design (CRD), which consists of 5 treatments and 4 replications. The treatments used are: K1= TKKS Trichocompos 25 ton/ha, K2= TKKS Trichocompost 50 ton/ha, K3= TKKS Trichocompost 75 ton/ha, K4= TKKS Trichocompost 100 ton/ha and K5= TKKS Trichocompost TKKS 125 ton/ha. Data were analyzed statistically using analysis of variance (ANOVA). Parameters those measured plant height, stem diameter, leaves numbers, root volume, plant dry weight and shoot to root ratio. The results suggest that, there were no significant effect of TKKS Trichocompost toward all parameters, except shoot to root ratio. Keyword : Seedling agarwood and Trichokompost TKKS